A Statistical Analysis of Multiple-Response Survey Data on Academic Journal Publishing Motivations - Zebulun, Gladys ThankGod; Owhondah, Providence Samuel; Wonu, Nduka (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2025)
This study investigates authors’ motivation to publish in academic journals using descriptive analysis of multiple-response survey data. A cross-sectional survey design was employed, and data were collected from 456 academic authors using a validated 15-item structured questionnaire with a Cronbach's Alpha index of 0.82, containing a multiple-response item on publication motivation. The instrument elicited motivation factors organized into five conceptual domains: editorial and review quality; visibility, credibility, and indexing; content and scholarly value; accessibility and cost considerations; and capacity building and incentives. Data were analyzed using frequency counts, percentages, and multiple-response bar-chart visualization, with results interpreted at the domain level. The findings reveal that editorial and review quality constitutes the most influential motivation for publication, with high endorsement of editorial team competence, ethical compliance, transparent peer review, and effective communication. Visibility and credibility factors, particularly DOI availability and indexing in reputable databases, also strongly motivated authors, though to a lesser extent than editorial quality. Content quality and scholarly value exerted a moderate influence, while accessibility and cost considerations were secondary, with greater emphasis on transparency than on publication fees. Capacity-building and incentive-related factors were the least influential motivations. The results demonstrate that authors’ publication decisions are predominantly quality- and credibility-driven rather than incentive-based. The study contributes to the literature by providing a domain-based descriptive assessment of multiple-response survey data on publishing motivation and offers practical insights for journal editors and publishers seeking to attract and retain high-quality scholarly submissions.